Bulky 2, 6-diphenylphenylsulfanyl substituents efficiently inhibit aggregation in phthalocyanines and tetrapyrazinoporphyrazines and control their photophysical and electrochemical properties. (January 2017) - Zimcik, Petr; Malkova, Anna; Hruba, Lenka; Miletin, Miroslav; Novakova, Veronika
Abstract: Octasubstituted zinc, metal-free and magnesium complexes of phthalocyanine and tetrapyrazinoporphyrazine bearing very bulky 2, 6-diphenylphenylsulfanyl substituents were synthesized. The substituents efficiently inhibited aggregation of the dyes and only monomers were detected even at a concentration of 200 μM solution in toluene. Photophysical data indicated influence of the heavy-atom effect – magnesium complexes were more fluorescent ( Φ F 0.40–0.51) and zinc complexes produced stronger the singlet oxygen ( Φ Δ 0.56–0.72) in both series of compounds. The presence of additional nitrogens in tetrapyrazinoporphyrazine core made it substantially more electron deficient when compared with corresponding phthalocyanine analogues. 2, 6-Diphenylphenylsulfanyl substituents also increased electron deficient character of the core and influenced the photophysical properties. Graphical abstract: Highlights: 2, 6-diphenylbenzenethiol was synthesized by Newman-Kwart rearrangement. Octasubstituted phthalocyanines and tetrapyrazinoporphyrazines were synthesized. The bulky substituents fully inhibited aggregation in toluene. 2, 6-diphenylphenylsulfanyl influenced photophysical and electrochemical properties.